INVESTIGATION OF BEHAVIOUR OF STEEL FIBER REINFORCED SELF COMPACTING CONCRETE - S. S. Waykar; Prof. R. M. Sawant (International Journal of Innovations in Engineering Research and Technology, 2021)
Self-compacting concrete (SCC) is considered as a concrete which can be placed and compacted under its self weight with little or no vibration effort and which is at the same time cohesive enough to be handled without segregation or bleeding. Chemical admixtures are, however, expensive, and their use may increase the materials cost. Savings in labor cost might offset the increased cost, but the use of mineral admixtures such as fly ash, blast furnace slag, or limestone filler could increase the slump of the concrete mixture without increasing its cost.Fly ash has high pozzolanic reactivity and low price as compared to silica fume and fly ash as it is a manufactured product. It reduces free drying shrinkage and restrains the shrinkage cracking width. It also helps in enhancing the compressive strength and durability of concrete.